Claim-Evidence-Reasoning-Based Interactive Modules to Improve Students’ Argumentation Skills on Salt Hydrolysis - Dewi, Citra Ayu; Muhali, Muhali; Joselevich, María (FKIP Universitas Lampung, 2025)
Claim–Evidence–Reasoning-Based Interactive Modules to Improve Students’ Argumentation Skills on Salt Hydrolysis. Scientific argumentation is a crucial element in chemistry education, enabling students to construct evidence-based explanations and engage in higher-order thinking. Nevertheless, students often struggle with abstract concepts such as salt hydrolysis, a topic that has received limited attention in the context of multimedia-based argumentation research. Objective: This study aims to develop and validate an interactive multimedia module designed to enhance students’ scientific argumentation skills and conceptual understanding of the salt hydrolysis topic. Methods: A research and development (R&D) approach was employed, following a modified educational development model consisting of seven stages: needs analysis, design, development, expert validation, revision, limited field testing, and final evaluation. The interactive module integrated visual simulations, narrative explanations, and interactive prompts based on the Claim–Evidence–Reasoning (CER) framework. Validation was conducted by three categories of experts, consisting of media experts, subject matter experts, and chemistry teachers, to evaluate the module's pedagogical feasibility, content accuracy, and technical feasibility. Findings: Expert validation indicated high feasibility, with average scores of 92.3% from media experts, 90.6% from subject matter experts, and 88.7% from practitioner teachers. In a pilot study involving 32 students, the average argumentation score increased from 56.8 (pre-test) to 78.2 (post-test), reflecting a gain score of 21.4. Classroom observations noted the increase in student engagement and participation. In addition, student feedback emphasized that the multimedia was user-friendly, visually appealing, and effective in assisting them in understanding complex topics, such as salt hydrolysis. Conclusion: Interactive multimedia modules, when designed using structured reasoning models such as the CER framework, can effectively foster the development of scientific argumentation skills and conceptual understanding. This study contributes to the field of technology-enhanced learning by providing a validated approach for integrating CER into digital science instruction. Future research should investigate the scalability and effectiveness of this approach across different scientific disciplines and educational levels. Keywords: interactive multimedia, salt hydrolysis, argumentation skills, chemistry education, claim–evidence–reasoning.